Risk of vasopressin use: a case of acute pulmonary oedema, post intramyometrial infiltration of vasopressin in laparoscopic myomectomy. Issue 12 (11th December 2019) - Barcroft, Jennifer Frances; Al-Kufaishi, Asmaa; Lowe, Justine; Quinn, Stephen
Abstract : A 34-year-old patient underwent a laparoscopic myomectomy, complicated by a profound episode of bradycardia and hypotension following intramyometrial infiltration of vasopressin (20 IU), promptly corrected with intravenous ephedrine (6 mg) and glycopyrrolate (200 µg). At extubation, pink frothy fluid was noted in the endotracheal tube; she was visibly distressed, desaturated to 89% in air and was coughing up pink stained fluid. Acute pulmonary oedema secondary to vasopressin was suspected. A tight-fitting oxygen mask (100%) with positive end expiratory pressure was applied and intravenous furosemide (20 mg) and diamorphine (4 mg, 1 mg increments) were administered to facilitate diuresis and oxygenation. Chest X-ray confirmed acute pulmonary oedema. Arterial blood gas demonstrated type 2 respiratory failure. Over 12 hours, the oxygen was weaned to 1 L/min. She demonstrated excellent diuresis. Troponin and brain-natriuretic peptide were elevated, but echocardiogram was normal. The cardiology diagnosis was vasopressin-induced coronary vasospasm, precipitating acute pulmonary oedema. She was discharged home on day 5.